Mechanisms of TonB-dependent protein import in Pseudomonas aeruginosa - Goult, J (2021)
The rise of multidrug resistance in several bacterial families is an emerging therapeutic crisis, with the potential to revert society to a pre-antibiotic era. Of particular concern is the opportunistic pathogen, Pseudomonas aeruginosa, a major causative agent of hospital-associated infections. As such, the development of novel therapeutics to target multidrug resistant P. aeruginosa is critical. Protein antibiotics synthesised by P. aeruginosa, known as pyocins, have recently become the focus of concerted efforts to develop new treatments to combat bacterial infections. Pyocins are fundamental for interbacterial competition, but the mechanisms by which they translocate across the Gram-negative cell envelope are poorly understood. The work presented in this thesis explores the mechanism by which two nuclease-type pyocins, pyocin S2 (PyoS2) and pyocin SN (PyoSN) exploit target proteins within the P. aeruginosa cell membrane to stimulate uptake. The components of the cellular envelope parasitised by PyoSN during import were identified, including a novel OM transporter, CntO. CntO is a 22-stranded β-barrel and virulence factor in P. aeruginosa that transports the metallophore pseudopaline across the OM. PyoSN eliminated a broad range of Pseudomonas clinical isolates, demonstrating its potent therapeutic potential. The PyoSN transporter binding domain was subsequently isolated (PyoSNNTD) and the crystal structure solved. PyoSNNTD possessed a kinked three-helical bundle motif, which is conserved with the PyoS2NTD structure. Finally, the global mechanisms of TonB-dependent pyocin import were investigated in atomistic detail using PyoS2 and its transporter FpvAI. The structural constraints imparted on protein import across the OM were identified, confirming partial unfolding of the PyoS2NTD is a requirement for translocation through FpvAI. Interestingly, structural flexibility of transport was much greater than expected, with a PyoS2 disulphide construct retaining translocation activity in vivo. Hence, this study demonstrates a conserved mechanism of import for TonB-dependent protein antibiotics through exploitation of energised nutrient transporters in the OM.